Improving Some of the Mechanical Properties of Epoxy Resin Based Polymer Supported by Low Carbon-Steel Fibers (Journal of University of Babylon for Engineering Sciences, 2019)
In the present study, specimens of composite material were prepared by Hand lay- up molding method. The epoxy resin was reinforced by low carbon steel fibrous at different weight ratios (2, 4, 6)% by the random distribution of steel fiber in the resin. Mechanical properties were studied through (Bending strength, Impact strength and Hardness) tests. The results showed an increase in bending strength of (63%) in the percentage of reinforcement (4%). As for the impact strength, the results also showed an increase of (15%) in the percentage of reinforcement (4 %) , while the rate of increase in the value of hardness was (18%) in the percentage of reinforcement(4%).